KAJIAN TUJUH POE ATIKAN PENDIDIKAN PURWAKARTA ISTIMEWA DALAM PERATURAN BUPATI NOMOR 69 TAHUN 2015 - Anggy Giri Prawiyogi (Latifah Pres, 2018)
Purwakarta Regency Government is one of the areas in West Java that continues to focus on restoring local wisdom that lives in its communities. One of them is by promoting the Poe Atikan Istimewa 7 Program Purwakarta Istimewa. The strengthening of his study in the implementation of character education in Purwakarta Regency includes a series of coaching and nurturing activities for students inside and outside the school at the basic education level to develop their own potential, mental, spiritual, noble character, and skills needed for themselves, society, nation and country . Data was obtained from literature studies, documentation, and using a descriptive analysis research approach.